REDISCOVERY OF ALDROVANDA VESICULOSA L. (DROSERACEAE), AN ENDANGERED PLANT, AFTER SIX DECADES IN INDIA FROM MANIPUR WITH STUDIES ON MICROMORPHOLOGY AND PHYSICO-CHEMISTRY OF WATER - Romita Devi Ngangbam; Naorem Premita Devi; Maibam Haripriya Devi; Potsangbam Kumar Singh (REINWARDTIA, 2019)
NGANGBAM, R. D., DEVI, N. P., DEVI, M. H. & SINGH, P. K. 2019. Rediscovery of Aldrovanda vesiculosa L. (Droseraceae), an endangered plant, from Manipur in India after six decades, with studies on micromorphology and physico-chemistry of water. Reinwardtia 18(2): 71‒80. — A small population of the aquatic insectivorous plant Aldrovanda vesiculosa L. of Droseraceae family was found growing in Yena pat, a small lake having an area of about 0.939 km2 in Bishnupur district, Manipur state, India. This marks its rediscovery in India after a long gap of 64 years. The present status of the species in the updated IUCN Red List of Threatened Species version 2018.2 is endangered and considered extinct from India. A general description and micromorpho-taxonomic studies are included. As the species is a bioindicator, physico-chemical studies of the water were also investigated so as to provide aid in both in-situ and ex-situ conservation strategies. Immediate conservation initiatives are warranted to maintain the species after its rediscovery.